Visitors’ satisfaction towards service quality at Paya Beach Spa and Dive Resort, Tioman Island - Agusli, Balqis Nabilah (2018)
This study was conducted to assess the visitors’ satisfaction towards the service quality offered by Paya Beach Spa and Dive Resort. Although this resort has a 3-star online rating reviews, it still lacks on the service quality resulting in many complaints and customers’ dissatisfaction. Due to monsoon season, money and time constraint, only 92 respondents were chosen using convenience sampling. From the questionnaires, data obtained were demographic characteristic and the visitors’ level of satisfaction towards the five attributes concerning the service quality. In answering the objectives of this study, data was analysed using descriptive analysis, correlation and multiple regression analysis. The result shows that the relationship between the visitors’ satisfaction and service quality are all significant at 0.01 level. It shows that human element and social responsibility in service quality are important attributes in deciding their level of satisfaction and factor for repetition of visit to the resort. Based on the result obtained from this study, it can be concluded that the findings and information be appropriately used as guidelines for the management of the resort to help increase visitors’ satisfaction.